Gelsolin-Cu/ZnSOD interaction alters intracellular reactive oxygen species levels to promote cancer cell invasion. - Tochhawng, L.; Deng, S.; Pugalenthi, G.; Kumar, A.; Lim, K.; Yang, H.; Hooi, S.; Goh, Y.; Maciver, S.; Pervaiz, Shazib; Yap, C. (Impact Journals LLC, 2016)
The actin-binding protein, gelsolin, is a well known regulator of cancer cell invasion. However, the mechanisms by which gelsolin promotes invasion are not well established. As reactive oxygen species (ROS) have been shown to promote cancer cell invasion, we investigated on the hypothesis that gelsolin-induced changes in ROS levels may mediate the invasive capacity of colon cancer cells. Herein, we show that increased gelsolin enhances the invasive capacity of colon cancer cells, and this is mediated via gelsolin's effects in elevating intracellular superoxide (O2.-) levels. We also provide evidence for a novel physical interaction between gelsolin and Cu/ZnSOD, that inhibits the enzymatic activity of Cu/ZnSOD, thereby resulting in a sustained elevation of intracellular O2.-. Using microarray data of human colorectal cancer tissues from Gene Omnibus, we found that gelsolin gene expression positively correlates with urokinase plasminogen activator (uPA), an important matrix-degrading protease invovled in cancer invasion. Consistent with the in vivo evidence, we show that increased levels of O2.- induced by gelsolin overexpression triggers the secretion of uPA. We further observed reduction in invasion and intracellular O2.- levels in colon cancer cells, as a consequence of gelsolin knockdown using two different siRNAs. In these cells, concurrent repression of Cu/ZnSOD restored intracellular O2.- levels and rescued invasive capacity. Our study therefore identified gelsolin as a novel regulator of intracellular O2.- in cancer cells via interacting with Cu/ZnSOD and inhibiting its enzymatic activity. Taken together, these findings provide insight into a novel function of gelsolin in promoting tumor invasion by directly impacting the cellular redox milieu.